14.4k views
0 votes
Hello please help me with this I need an answer immediately thank you so much see image

Hello please help me with this I need an answer immediately thank you so much see-example-1
User Alkersan
by
5.1k points

1 Answer

2 votes

For this case, we know that:


PA = PB

Then, by Pythagorean theorem (right triangle on the right) we have:


CP ^ 2 = CB ^ 2-PB ^ 2

So, again using the Pythagorean theorem (right triangle on the left) we have:


CA ^ 2 = CP ^ 2 + PB ^ 2

Substituting values:


CA ^ 2 = (CB ^ 2-PB ^ 2) + PB ^ 2

Rewriting:


CA ^ 2 = CB ^ 2


CA = CB


CA = 15

Answer:

The value of CA is given by:


CA = 15

User Imran Shoukat
by
6.5k points